Ethical and psychological issues of surrogacy - Zhou Chaoyun (Sichuan jingshen weisheng, 2021)
The purpose of this article is to discuss the ethical and psychological issues of surrogacy. A lot of psychological issues will arise as a result of the many complicated and controversial difficulties in law， science， morality and public policy， and therefore a study of the ethical and psychological issues of surrogacy will contribute to a better understanding and management of these issues.